Toxicity Test of Ethanol Extract of Gagatan Harimau Leaves (Vitis Gracilis BL.) on Artemia Salina Leach Larvae Using Brine Shrimp Lethal Test (BSLT) Method - Surbakti, Chemayanti; Rimayani Nasution, Lisda; Ni Rudang, Singgar; Cintya, Henni; Vany, I.; Agnes, P.A.T.; Elsa, S.E.S. (International Journal of Science, Technology & Management, 2023)
Gagatan harimau leaves (Vitis gracilis BL) is a plant contains several secondary metabolite compounds, namely alkaloids, glycosides, tannins, saponins and flavonoids and has been used traditionally to treat diarrhea, infectious diseases, inflammation and diabetes. The aim of this study was to to determine data on the percentage of deaths and the LC50 value of the ethanol extract of the Gagatan harimau (Vitis gracilis BL) against Artemia Salina Leach using the Brine Shrimp Lethality Test (BSLT) method. The method used is the Brine Shrimp Lethality Test (BSLT) with concentrations of 180 ppm; 200 ppm; 220ppm; 240ppm; 260ppm; 280ppm; 300 ppm and 0 ppm as negative controls each replicated three times. At each concentration, 10 Artemia salina Leach larvae were used as test animals, each concentration was 48 hours old. The toxic effect of the extract was determined by the percentage mortality of Artemia salina Leach larvae using probit analysis (LC50). The results of this research gave the linear regression equation Y = 11.674x-68.227. Therefore, the LC50 value is 6.275 and the LC50 gets a value is 187.068 ppm. Research on the toxicity of Gagatan harimau (Vitis gracilis BL.) ethanol extract using the BSLT (Brine Shrimp Lethality Test) method in this study is toxic because the LC50 is < 1000 ppm so it has the potential to be anticancer.